Development of E-Library Applications for Sociology Learning - Szauli Putra, Berkah Adityo (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2022)
The background of this study is the lack of learning resources owned by students during the sociology learning process. The purpose of this study is to produce a feasible and practical E-Library application for learning Sociology. The type of research used in this research is Research and Development (R&D). The development model used in this development research is the ADDIE development model. The research instruments used included: validation sheets and practicality questionnaires. Data collection techniques are carried out using observation, tests, questionnaires, and documentation. The results showed that the media validation test for the media expert's assessment of the E-Library 1 application was 96%